2005
DOI: 10.1590/s0006-87052005000400019
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de molibdênio e cobalto na semente para cultivo da soja

Abstract: A aplicação de molibdênio e cobalto nas sementes tem sido uma prática comum para o cultivo de soja no Brasil. O objetivo deste trabalho foi avaliar o efeito da aplicação de molibdênio e cobalto na nodulação da soja, na nutrição da planta e seus reflexos sobre o rendimento de grãos. O experimento foi realizado no município de Ponta Grossa (PR), em Latossolo Vermelho textura argilosa, com pH (CaCl2 0,01 mol L-1) 5,2. O delineamento experimental empregado foi o de blocos completos ao acaso, em esquema fatorial 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
7
0
7
Order By: Relevance
“…Sfredo and Oliveira (2010) pointed out that Mo absorption by soybean plants occurs predominantly as MoO 4 2− when soil pH is equal to or higher than 5.0. It was confirmed by Marcondes and Caires (2005), who observed no influence of Mo applied to seeds on nodulation, N content in leaves and grains, and productivity in a soil with a pH of 5.2. Therefore, this result is in accordance with these studies, which showed that an increased soybean productivity was observed when soils had a pH lower than 5.0, proving that Mo application via seed or leaf supply soybean plants when there is no availability of soil Mo, which did not occur in the present study.…”
Section: Resultsmentioning
confidence: 66%
“…Sfredo and Oliveira (2010) pointed out that Mo absorption by soybean plants occurs predominantly as MoO 4 2− when soil pH is equal to or higher than 5.0. It was confirmed by Marcondes and Caires (2005), who observed no influence of Mo applied to seeds on nodulation, N content in leaves and grains, and productivity in a soil with a pH of 5.2. Therefore, this result is in accordance with these studies, which showed that an increased soybean productivity was observed when soils had a pH lower than 5.0, proving that Mo application via seed or leaf supply soybean plants when there is no availability of soil Mo, which did not occur in the present study.…”
Section: Resultsmentioning
confidence: 66%
“…Pesquisa desenvolvida por Marcondes & Caíres (2005) concluíram que a aplicação de cobalto e molibdênio nas sementes de soja não influenciou no número de vagens por planta, nos teores de nitrogênio nos grãos, altura de planta, e na produtividade. O cobalto influenciou negativamente na altura de planta e na produtividade de grãos, em razão da fitotoxidez deste elemento.…”
Section: Resultsunclassified
“…Segundo Marcondes;Caires (2005), o tratamento das sementes de soja com Co reduz linearmente a altura de plantas, devido a fitotoxicidade do elemento para a cultura da soja.…”
Section: Teores Foliares De N Co E Mounclassified